The Experiment of University of Science and Technology in the Field of Quality Assurance for Academic Performance - Musleh, Abdullatif; Zahary, Ammar (The Online Journal of Quality in Higher Education, 2015)
During the last 10 years, University of Science and Technology (UST) in Yemen has developed a special model for quality which has been inspired from the international experiments in the field quality in higher education taking into consideration the privacy and the culture of the zone. This paper presents this model which involves several tools, procedures, quality measures, and Key Performance Indicators (KPIs). The model was developed based on the organizational model so that it involves 4 dimensions of the UST educational system: inputs, processes, outcomes, and feedback. This model is implemented since the academic year 2003/2004 until now and it has subjected to continuous developing and enhancement. As a result of applying this model, a remarkable quality of service has achieved and the UST has grown dramatically in terms of number of students, colleges, programs and international partnerships.